2017
DOI: 10.2196/jmir.7697
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Engagement With a Web-Based Lifestyle Intervention Following Provision of Coronary Heart Disease Risk: Mixed Methods Study

Abstract: BackgroundWeb-based interventions provide the opportunity to combine the tailored approach of face-to-face interventions with the scalability and cost-effectiveness of public health interventions. This potential is often limited by low engagement. A number of studies have described the characteristics of individuals who engage more in Web-based interventions but few have explored the reasons for these variations.ObjectiveWe aimed to explore individual-level factors associated with different degrees of engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In group guidance, participants received information regarding weight‐loss strategies and support for goal setting. As for the emails, previous studies reveal that remainder emails facilitate engagement with health programs . In the present study, group guidance and monthly emails were provided by the same provider who monitored participants’ achievement, thus personalizing the expectation of adherence and harnessing the trust relationship between participants and provider.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In group guidance, participants received information regarding weight‐loss strategies and support for goal setting. As for the emails, previous studies reveal that remainder emails facilitate engagement with health programs . In the present study, group guidance and monthly emails were provided by the same provider who monitored participants’ achievement, thus personalizing the expectation of adherence and harnessing the trust relationship between participants and provider.…”
Section: Discussionmentioning
confidence: 90%
“…As for the emails, previous studies reveal that remainder emails facilitate engagement with health programs. 22,37 In the present study, group guidance and monthly emails were provided by the same provider who monitored participants' achievement, thus personalizing the expectation of adherence and harnessing the trust relationship between participants and provider. Previous research has identified time constraints and increased workload as barriers to Internet-based health intervention with in-person support 38 ; the low-intensity program provided to SSG can address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…The predictors in our model (eg, helpfulness of modules and features) relate to engagement only indirectly. Other studies involving Web-based programs have used more direct engagement measures, such as the number of sessions completed [ 24 ], time to last engagement with the website, or the number of hits or time spent online [ 25 ], whereas physical activity programs have used step counts completed [ 26 ]. Future studies experiencing low response rates for final surveys should attempt to incorporate these direct measures of engagement as control variables.…”
Section: Discussionmentioning
confidence: 99%
“…Providing online programs via the Internet allows remote access to medical and public health practices, which is supported by home computers as well as mobile devices, such as mobile phones (smartphones), remote patient monitoring devices, and personal digital assistants (PDAs), such as tablets (Cohen et al, 2017; Hood, 2017; WHO, 2011). The advantages of online programs include reductions in geographical constraints (Revenäs et al, 2016), access to medical information and medical care 24 hours a day, 7 days a week (Hood, 2017; Usher-Smith et al, 2017; van Kruijssen et al, 2015), and the benefit of privacy (Stinson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%